Upaya Meningkatkan Hasil Belajar Servis Atas pada Bolavoli Melalui Metode Team Games Tournament (TGT) pada Siswa Kelas XI AKL 1 SMKN 1 Sanggau: Kristina Merry Silla, Rajidin, Henry Maksum - silla, kristina merry (Journal Sport Academy, 2024)
This research aims to improve learning outcomes for top serves in volleyball games through the team games tournament method for class XI AKL 1 SMKN 1 Sanggau students. This type of research is classroom action research (PTK) with two cycles. The research objects were students of class XI AKL 1 SMKN 1 Sanggau. Data collection techniques use student test results. From the pre-cycle test, it can be seen that student learning outcomes are still very poor, there are 21 students in the incomplete category or 65.62%, then in the completed category there are 11 students or 34.37% of the total 32 students. After I used the team games tournament method in cycle I there were 16 students or 50% of the student category who completed, in the category of students who did not complete there were 16 students or 50%. Meanwhile, based on the results of the final test in cycle II of 32 students of class So, it can be concluded that using the team games tournament method has been proven to improve students' volleyball service learning outcomes. This is proven by the team games tournament method, volleyball service skills have seen a very good improvement, that is, students' scores have increased in each cycle.